2022
DOI: 10.1186/s40545-022-00450-y
|View full text |Cite
|
Sign up to set email alerts
|

Practice of non-pharmaceutical interventions against COVID-19 and reduction of the risk of influenza-like illness: a cross-sectional population-based study

Abstract: Introduction While the widespread implementation of the non-pharmaceutical interventions was intended to contain the COVID-19 pandemic, such measures could be also effective in limiting the spread of other respiratory infections. This study aimed to examine the association between the implementation of personal protective measures and the occurrence of influenza-like illnesses (ILI) in the general population. Methods An online retrospective cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…At the inception of the COVID-19 pandemic, nonpharmaceutical interventions such as masking, physical distancing, and hand hygiene were the only ways to deter the infection (19)(20)(21). Vaccines, as a mock infection to coach the immune system to defend against the natural infection, were developed at an unprecedented speed and the Pfizer-BioNTech and the Moderna COVID-19 vaccines were emergently authorized within a year in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…At the inception of the COVID-19 pandemic, nonpharmaceutical interventions such as masking, physical distancing, and hand hygiene were the only ways to deter the infection (19)(20)(21). Vaccines, as a mock infection to coach the immune system to defend against the natural infection, were developed at an unprecedented speed and the Pfizer-BioNTech and the Moderna COVID-19 vaccines were emergently authorized within a year in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Although the quantity of literature on COVID-19 in prison offers hope that the spread of infectious diseases in jails and prisons will continue to receive more attention, the dearth of literature on influenza should serve as a warning of how easily incarcerated and detained people are forgotten when an emergency no longer accentuates the dire nature of infectious diseases in detention facilities. Given similar pathways of transmission between the two viruses, COVID-19 mitigation interventions in jails and prisons can likely be applied to stop the spread of influenza and other respiratory viruses with similar positive results (Huang et al, 2021; Solomon et al, 2020; Youssef et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 1–3 Evidence from several countries has shown that these measures could be effective in reducing the incidence and prevalence of COVID-19. 4–6 However, it was quickly realized that sustaining NPIs for extended periods of time is practically impossible to achieve and is associated with dire consequences on the economy, education systems, and mental health. 7 , 8 Mass public vaccination was thus considered the most effective strategy to control the COVID-19 pandemic and was later recommended by the World Health Organization (WHO) and adopted by the majority of countries worldwide.…”
Section: Introductionmentioning
confidence: 99%